Current management and treatment of patients with stable coronary artery diseases presenting to cardiologists in different clinical contexts: A prospective, observational, nationwide study. (January 2018) - De Luca, Leonardo; Temporelli, Pier Luigi; Lucci, Donata; Gonzini, Lucio; Riccio, Carmine; Colivicchi, Furio; Geraci, Giovanna; Formigli, Dario; Maras, Patrizia; Falcone, Colomba; Di Lenarda, Andrea; Gulizia, Michele Massimo
Background: Stable coronary artery disease (CAD) is a leading cause of mortality worldwide. Few studies document the complete sequence of investigation of the overall stable CAD population during outpatient visits or hospitalisation. Aim: To obtain accurate and up-to-date information on current management of patients with stable CAD. Methods: START (STable coronary Artery diseases RegisTry) was a prospective, observational, nationwide study aimed at evaluating the presentation, management, treatment and quality of life of stable CAD patients presenting to cardiologists during outpatient visits or discharged from cardiology wards. Results: Over a 3-month period, 5070 consecutive patients were enrolled in 183 participating centres: 72% managed by a cardiologist during outpatient or day hospital visits and 28% discharged from cardiology wards. The vast majority of patients (87%) received a coronary angiography (86% of patients managed during outpatient visits and 90% during hospitalisation; p < 0.0001). Outpatients more frequently received optimal medical therapy (OMT; i.e. aspirin or thienopyridine, β-blockers and statins) compared to hospitalised patients (70.2% vs 67.1%; p = 0.03). A personalised diet was prescribed in 58% (60.5% in outpatients and 52.9% in those admitted to hospitals; p < 0.0001), physical activity programmes were suggested in 65% (69.4% and 54.3%; p < 0.0001) and smoking cessation was recommended in 71% of currently smoking patients (73.2% and 65.2%; p = 0.02). Conclusions: In this large, contemporary registry, patients with stable CAD discharged from cardiology wards more commonly underwent diagnostic imaging procedures and less frequently received OMT or lifestyle modification programmes compared to patients manged by cardiologists during outpatient visits.